From words to action: the development of the Neglected Tropical Disease Inclusion Score Card (NISC) - Robin van Wijk; Surya J. M. Baudoin; Bernice Ejiogu; Upasana Regmi; Mathias Duck; Ibrahim Rabiu; Constanze Vettel; Heleen Broekkamp; Roos Geutjes; Ruth M. H. Peters; Ida J. Korfage (Infectious Diseases of Poverty)
Abstract Background The importance of patient participation in designing and delivering services for persons affected by neglected tropical diseases (NTDs) has gained increasing recognition. Responding to this, persons affected by NTDs urged NTD-focused non-governmental organisations (NGOs) to take action. These NGOs are pivotal in addressing healthcare disparities and reaching marginalised communities. To address the insufficient progress on participation, a participatory initiative was launched to develop a tool designed to support NGOs in fostering inclusion and ensuring the meaningful engagement of affected persons in their organisational decision-making processes. Methods This research used an iterative, mixed-methods approach involving stakeholder input, semi-structured interviews, and surveys across two phases. Phase 1 included exploratory workshops with persons affected by NTDs and NTD NGO employees which led to the development of a first draft of a self-assessment tool. Phase 2 involved piloting the tool in NTD NGOs. Data were gathered via pre- and post-pilot interviews and surveys. Thematic analysis was used for the qualitative data and descriptive analysis for the quantitative data. Results In phase 1, exploratory workshops revealed that meaningful participation involves creating environments where affected persons can openly share priorities and build their capacity. Workshop participants emphasised the need of inclusion at all stages of NGO activities. These insights informed the draft NTD Inclusion Scorecard (NISC), covering six domains. In phase 2, ten pilot sessions were conducted, feedback was gathered from 22 interviewees and 43 survey participants, focusing on the NISC’s usability and relevance. While feedback on the NISC was positive, participants highlighted the need for contextualisation, organisational commitment, and adding a communication domain to the NISC. Conclusions The NISC is a self-assessment tool for NTD organisations, designed to enhance internal decision-making by fostering awareness of the importance of including the perspectives of persons affected by NTDs. By using the NISC, NGOs can identify gaps in inclusion and participation, improve their decision-making processes and provide services that are relevant and impactful for persons affected by NTDs. This tool provides insights that can guide NGOs in strengthening their role in promoting inclusion and increasing the effectiveness of their programmes. Graphical Abstract